A SIXTEENTH-CENTURY OTTOMAN SCHOLAR IN THE FOOT-STEPS OF IBN TAYMIYYA AND AN OPPONENT OF IBN 'ARABI: CHIWIZADA MUHYI AL-DIN SHEIKH MEHMED EFENDI - Gel, Mehmet (Bursa Ilahiyat Vakfi, 2013)
One of the Ottoman scholars in the sixteenth century who opposed the view of the famous Sufi Munyi al-Din Ibn 'Arabi was Chiwizada Munyi al-Din Sheikh Mehmed Efendi (d. 954/1547). He served as sheikh al-islam in the reign of Sulayman the Magnificent for a short time. He stood out for his criticisms against some Sufis of his time and was even dismissed from the rank of sheikh al-islam because of these criticisms, according to some reports. In this paper, I will examine Chiwizada's criticisms of Munyi al-Din Ibn 'Arabi, who was at the top of the Sufis he opposed, in terms of their historical-intellectual roots.
Keywords: Chiwizada; Ibn 'Arabi; Ibn Taymiyya; Sheikh Bali Al-Sofyawi; Fusu Al-Hikam